Effect of hot air on Deglet Noor palm quality parameters and on Ectomyelois ceratoniae. (July 2016) - Ben-Amor, Rihab; de Miguel-Gómez, María Dolores; Martínez-Sánchez, Ascensión; Aguayo, Encarna
Abstract: Insect infestation caused by Ectomyelois ceratoniae or carob moth is one of the main postharvest problems that lead to a decrease of marketable quality of dates. The control of carob moth is a mandatory process for exported fruits, and the main chemical method used to prevent pest diseases of palm date is methyl bromide. However, its use is being restricted due to direct, harmful effects to the environment, and indirect effects on humans. Hot air treatments (HATs) could be physical alternatives to methyl bromide and other chemicals. Three HATs (55 °C for 30 min, 60 °C for 15 min, 60 °C for 20 min) were studied on Deglet Noor date fruits when stored for 45 d at 2 °C followed by a retail period of 4 d at 23 °C. The results showed that the use of HATs led to 100% E. ceratoniae larvae mortality in naturally-infested date. These HATs did not cause any damage on fruit quality and reduced mesophilic bacterial counts (<1 log CFU g −1 ). These HATs, especially the combination of highest temperature and longer time of application (60 °C for 20 min), decreased the antioxidant activity (25% in DPPH and 14% in FRAP assay). Storage time also had a significant impact, reducing color (h°), antioxidant activity, and total phenolic content of date fruits (39%). When this storage was accompanied by a retail period at 23 °C, the firmness and sensorial parameters of date fruits was significantly reduced. Nevertheless, all date fruits from HATs and control treatments maintained their marketability quality for 45 d at 2 °C followed by a retail period of 4 d at 23 °C. Results show that HATs are a physical, non-chemical, treatment for E. ceratoniae larvae mortality that maintained date fruits' postharvest quality. Graphical abstract: Highlights: Hot air treatments (HATs) cause 100% Ectomyelois ceratoniae mortality in date fruits. HATs did not cause any heat damage on fruits and reduced mesophilic bacterial counts. HATs, especially the 60 °C for 20 min treatment, decreased the antioxidant activity. HATs are a physical alternative to methyl bromide that maintains the postharvest quality.